Understanding the genetic mechanisms of Clostridium difficile toxin regulation and clinical relapse - Lister, Michelle M. (2018)
Clostridium difficile is the leading cause of health care associated diarrhoea and remains a burden for the NHS. Disease symptoms can range from mild diarrhoea through to fulminant pseudomembranous colitis, resulting in mortality for some patients. Recurrence is a major problem and estimates are that 20% of all patients with disease will either relapse (with the same strain) or have a re-infection (with a different strain). Arguably, the main virulence factors are toxins A (TcdA) and toxin B (TcdB) which cause disease symptoms. The genes encoding TcdA and TcdB are located within the pathogenicity locus (PaLoc) along with three accessory genes; tcdR, tcdE and tcdC. The regulatory network has been studied but we aimed to add to this knowledge by using two under investigated strains R20291 a so-called hypervirulent strain and VPI 10463 a strain known to produce higher levels of toxin. Two different methods of investigation were employed during this study to improve our understanding of both the regulation of TcdA / TcdB but also the genetic mechanisms behind clinical relapse. These methods were; using forward and reverse genetic analysis to assess phenotypic differences and using bioinformatics to identify genes and / or single nucleotide variants (SNP) that may play a role. Using a combination these methods we have identified potential regulators of toxin production in both strains. We have also identified unique genes and SNPs that might provide a fitness benefit to strains of C. difficile that were isolated from patients who had suffered relapse episodes.